2004
DOI: 10.1073/pnas.0307346101
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol inhibits luteinizing hormone-releasing hormone release by activating the endocannabinoid system

Abstract: We hypothesized that ethanol (EtOH) might act through the endocannabinoid system to inhibit luteinizing hormone-releasing hormone (LHRH) release. Therefore, we examined the mechanism by which EtOH and anandamide (AEA), an endogenous cannabinoid, inhibit LHRH release from incubated medial basal hypothalamic explants. In previous work, we demonstrated that EtOH inhibits the N-methyl-D-aspartic acid-stimulated release of LHRH by increasing the release of two neurotransmitters: ␤-endorphin and ␥-aminobutyric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 37 publications
6
27
0
Order By: Relevance
“…Furthermore, we have recently demonstrated that AEA inhibits the forskolin-stimulated LHRH release in male rats (16). In the present work we observed that AEA inhibited LHRH release from MBH of males but had no effect on the hypothalamic LHRH release in OVX rats.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Furthermore, we have recently demonstrated that AEA inhibits the forskolin-stimulated LHRH release in male rats (16). In the present work we observed that AEA inhibited LHRH release from MBH of males but had no effect on the hypothalamic LHRH release in OVX rats.…”
Section: Discussionsupporting
confidence: 58%
“…We have recently demonstrated in male rats that AEA increased the release of GABA, a neurotransmitter involved in the inhibition of LHRH release (16). Thus, a stimulation of GABA release could be involved in the inhibition of basal LHRH release by AEA in males.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Postsynaptic GABA receptors, located on GnRH neurons, are not activated, and as a consequence, GnRH is not released. Interestingly enough, the inhibitory effect of AEA was higher than that of 2-AG [58,59]. Olah and coworkers postulated that the difference between the effects of AEA and 2-AG on the serum levels of LH is due to the difference in receptor activation as AEA can activate both CB1 and TRPV1 receptors while 2-AG acts only on the CB1 receptor [60].…”
Section: Ecs and The Hypothalamus-pituitary-gonadal Axismentioning
confidence: 99%
“…Having demonstrated the presence of CB1 receptors in the MBH, we studied the effect of AEA on LHRH release. Firstly, we showed that AEA (10 -9 M ) decreased by 70% the N-methyl D -aspartic acid (NMDA)-stimulated LHRH release from MBH incubated in vitro [10] . Secondly, we demonstrated that the same concentration of AEA significantly decreased the forskolin (FRSK)-induced cyclic AMP (cAMP) content and LHRH release.…”
Section: Endocannabinoids In Tnf-mentioning
confidence: 98%